Proposing a model on risk mitigation in IT governance - Che Pa, Noraini; Anthony Jnr, Bokolo; Nor, Rozi Nor Haizan; Jusoh, Yusmadi Yah (School of Computing, Universiti Utara Malaysia, 2015)
Risk mitigation is the core process in IT Governance. Due to the fact that application of IT Governance systems may sustain risks, organizations use risk mitigation to solve risks within IT systems and provide sufficient means to treat these risks. Risk mitigation is necessary to ensure a successful IT Governance implementation. The risk mitigation process comprises of risk identification, risk decision, risk treatment and risk monitoring. The aim of this paper is to present the new risk mitigation models’ components and metrics for measuring the risk in IT Governance.